Применение метода эксцессов для получения достоверной оценки расширенной неопределенности. - Захаров, И. П.; Климова, Е. А. (Харківький університет повітряних сил, 2014)
A method of expanded uncertainty calculating is described. The results of coverage factor evaluation by the instrumentality of developed method with the results obtained by Monte Carlo simulation are compared.
Application of kurtosis method to obtain reliable estimate of expanded uncertainty
Keywords: expended uncertainty; coverage factor; kurtosis method